Integrative Methods for Sustainable Competitive Advantage - Gheorghe TOLU; Daniel GHICULESCU (Communications of International Proceedings, 2020)
The paper deals with some integrative methods applied by a Romanian organization, manufacturer of electrical discharge machines, aiming at Sustainable Competitive Advantage (SCA). Some aspects of the strategic management process are presented, emphasizing the stage when the integrative methods must be applied. Some fundamental aspects of Customer Matrix, Producer Matrix and Risk Cube are presented. Finally, they are applied for the mentioned above organization, determining some solutions leading to SCA.
Keywords: Sustainable Competitive Advantage; Customer Matrix; Producer Matrix; Risk Cube.